Effect of Nutrition Interventions on Knowledge and Adoption Feasibility of Gluten Free Products by Celiac Disease Patients - Jyoti; Veenu Sangwan, Varsha Rani (Indian Journal of Extension Education, 2022)
The study was undertaken with the objective to improve the nutritional knowledge and technical skill of celiac disease patients. Since celiac is a disease that occurs due to gluten allergy and is quite prevalent these days. Hence this study was planned to promote nutrition education to celiac patients and give them training on the preparation of gluten-free products during 2020-21. Thirty celiac disease patients were selected randomly using the snowball method. Lectures cum demonstrations for the preparation of gluten-free quinoa-based laddoo, upma, porridge, and pulao were given. Leaflets containing the recipes for preparation and nutritional importance of quinoa products were distributed. Pre-exposure scores (1.00 to 1.55) depicted that respondents had very less knowledge of the celiac disease, its causes, gluten-free foods, quinoa, and its products, price of quinoa, nutritional importance, and medicinal uses of quinoa seeds. A significant increase (P<0.01) was observed in knowledge scores (1.71 to 2.00) of respondents after imparting nutrition education. All the quinoa products i.e. laddoo, porridge, pulao, and upma were liked by them and they felt that they can easily make these products.